Implementation of the Baduy Tribe's Inheritance System in Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province - Maganda, Edwin; Sitompul, Roswita; Rizal, Said (IJBLE Scientific Publications Community Inc., 2024)
The Muslim Baduy community basically adheres to the customs and customs they adopted from their ancestors. The inheritance system used in Baduy customary inheritance uses a bilateral system, namely from father to mother who are equally powerful. The problem that will be discussed is how to implement inheritance in the Baduy Dalam tribe community. The type of research used in this research is normative juridical legal research, namely library research which only focuses on written statutory regulations, so this research is very closely related to libraries because it requires secondary data. The fundamental difference between the inheritance law of the Baduy community and Islamic inheritance law lies in Pikukuh which is the basis for the unwritten inheritance distribution rules which in Islamic inheritance law are clearly based on the Al-Quran and As-Sunnah. Apart from that, there are similarities between Baduy inheritance law and Islamic inheritance law in that the heirs are the descendants of the person who died and the inheritance can only be distributed after the death of the testator. However, the Baduy community does not distribute inheritance to the lineage and above.